De quem é o vestibular?: a mãe frente à diferenciação do filho - Oliveira, Inalda Maria Dubeux Andrade de (2000)
The purpose of the present research was to understand the nature of the feelings demonstrated by mothers who are experiencing the separation/individuation process of an adolescent son (daughter) as symbolized by the vestibular entrance exam and to analyze the possible effect of these feelings on the vocational choice of their children. The study had the collaboration of 8 mothers, ages between 39 to 43, which were going through the vestibular situation for the first time. Using semi-directive interviews the research analyzed the following dimensions: predominant feelings in face of the vestibular situation; the mother s perception of the son s (daughter s) differentiation process; their reaction to autonomy manifestations on the son s (daughter s) part; the meaning the mother attributes to the vestibular; a possible relation between the mother s career choice and the moment the adolescent faces and the mother s perception of possible changes in her life as a result of the vestibular situation. Each interview was first analyzed as an individual case study and afterward they were all compared to each other in relation to the above mentioned dimensions. It was observed that the high level of anxiety the mothers demonstrated in face of the situation represented a sum of feelings related to the difficulty of elaborating the separation/individuation process in their children. Mothers tended to: 1) perceive their sons (daughters) as dependent and immature; 2) identify with the adolescents in a symbiotic manner of relation and to deny possible changes in their own lives in view of the new situation; 3) interfere directly in their son s (daughter s) career choice; 4) perceive the vestibular situation as a victory or accomplishment mainly for themselves, instead of the adolescent s, which denoted how some mothers feel that they re valued by their children s performance. The research concluded that this resistance in face of the differentiation process interferes in a negative way in their children s career choices and contributes to difficult the elaboration of a personal life project by adolescents. It was empathized that such influence is mainly due to the moment when the vestibular takes place in Brazil, in which the adolescent is chronologically imature, fact that contributes to difficult the separation process